ANALISIS DINAMIKA PENYEBARAN COVID-19 DENGAN LAJU INSIDEN NONLINEAR - Nurul Qorima Putri; Paian Sianturi (MES: Journal of Mathematics Education and Science, 2021)
This research is focused on discussing the SEIQRS epidemic model for the spread of the COVID-19 disease with a nonlinear incidence rate. From the result of analysis of the SEIQR model obtained two equilibrium point these are diseases free equilibrium points and endemic equilibrium point. Then, the analysis of the completion behavior is done by using eigenvalues and stability around equilibrium point, the obtained result of the diseases free equilibrium point has two stability traits are saddle point, and stable. The stability diseases free equilibrium will be stable when  R0  1, if R0 1 then the equilibrium point is not stable (saddle point) and conversely the positive endemic equilibrium point will be spiral stable. In numerical analysis, it is done by varying the parameter values and using the fourth order runge-kutta approach.